CHARACTERISTICS OF THE USE OF INNOVATIVE INVENTORY IN THE PROCESS OF PHYSICAL EDUCATION OF SCHOOL YOUTH (Physical Culture and Sport: Scientific Perspective, 2024)
Modern education is constantly evolving, adapting to changes in society and technological progress. One important field that is not left behind in this process is physical education. It is a key component in the development of a student's personality, influencing their physical, emotional, and social well-being. Contemporary physical education requires current approaches and innovative tools that contribute to enhancing the quality of learning and developing students' physical skills. One key aspect of this process is the use of innovative equipment. Physical education classes in educational institutions are as important as other subjects, serving as a vital tool for the holistic development of a child. Through sports activities, students develop teamwork skills, discipline, leadership potential, tolerance, and healthy competition.The study aimed to theoretically analyze the use of innovative equipment in physical education classes and determine interest in its utilization.The initial survey confirmed our suspicions that the majority of respondents were unfamiliar with equipment such as balance pillows (89.5%), TRX straps (80.2%), and jumping trampolines (86%). This indicates that this equipment could be beneficial for improving children's physical abilities.Following the initial survey, we introduced the innovative equipment and conducted a workshop on its usage and its impact on the body during regular sessions.The conclusion of this event was a follow-up survey aimed at determining interest in engaging with the presented equipment.Analyzing the survey results, we found that 74 (86%) respondents had a positive attitude towards implementing this equipment in physical education classes, with only 2 (2%) responding negatively. Therefore, it can be concluded that children respond positively to the introduction of new innovative activities and equipment. During the workshop, all participants showed interest and enthusiasm for exercises using the described equipment.In our opinion, diversifying activities with the use of step platforms, fitness bands, balance pillows, TRX, and jumping trampolines can motivate students to attend physical education classes and engage in independent workouts, diverting them from sedentary lifestyles and increasing physical activity throughout the week.
Keywords: physical education; schoolchildren; step platform; balancing pillow; fitness rubber band; TRX; trampoline jumping